STRATEGI KOMUNIKASI PEMASARAN THRIFT SHOP MELALUI TIKTOK DALAM MENINGKATKAN PENJUALAN: STUDI KASUS AKUN MIMINKERANJANGVINTAGE - Melatiningsih, Budhi Sri (Cahaya Ilmu Bangsa, 2025)
This research aims to analyze the marketing communication strategies implemented by the thrift shop Miminkeranjangvintage through the social media platform TikTok to enhance sales. In the digital era, social media like TikTok has become an effective tool for reaching a broad consumer base, particularly among young people, due to its interactive and creative nature. This research employs a case study approach with qualitative methods, involving in-depth interviews with relevant informants and content analysis of the Miminkeranjangvintage TikTok account. The findings reveal that the use of TikTok Live features, creative content, and direct interaction with the audience are key elements in Miminkeranjangvintage marketing strategy. This strategy successfully increased brand visibility, fostered relationships with consumers, and boosted sales of quality thrift products. Additionally, the study identifies both internal factors, such as user motivation, and external factors, such as digital trends, influencing the success of marketing communication. The conclusion of this research is that leveraging TikTok as a marketing communication channel presents significant opportunities for thrift shop businesses to compete in an increasingly competitive market. These findings contribute to the development of digital marketing strategies for small and medium enterprises in Indonesia. Penelitian ini bertujuan untuk menganalisis strategi komunikasi pemasaran yang diterapkan oleh Thrift Shop Miminkeranjangvintage melalui platform media sosial TikTok dalam meningkatkan penjualan. TikTok menjadi alat komunikasi pemasaran yang efektif, terutama di kalangan anak muda, karena sifatnya yang interaktif dan kreatif. Penelitian menggunakan pendekatan studi kasus dengan metode kualitatif melalui wawancara mendalam dan analisis konten akun TikTok Miminkeranjangvintage. Hasil penelitian menunjukkan bahwa penggunaan fitur TikTok Live, konten kreatif, dan interaksi langsung dengan audiens merupakan elemen kunci dalam strategi pemasaran Miminkeranjangvintage. Strategi ini berhasil meningkatkan visibilitas merek, membangun hubungan dengan konsumen, dan mendorong penjualan produk thrift berkualitas. Faktor internal seperti motivasi pengguna serta faktor eksternal seperti tren digital turut memengaruhi keberhasilan komunikasi pemasaran. Kesimpulan penelitian ini adalah bahwa pemanfaatan TikTok sebagai saluran komunikasi pemasaran memberikan peluang besar bagi bisnis Thrift Shop untuk bersaing di pasar yang semakin kompetitif. Temuan ini memberikan kontribusi bagi pengembangan strategi pemasaran digital bagi usaha kecil menengah di Indonesia.